Implementasi Manajemen Perubahan untuk Mendukung Kesejahteraan karyawan Generasi-Z di tempat kerja - Amelia, Lia; R Deni Muhammad Danial; Erry Sunarya (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Organizational change is a complex challenge and requires a useful approach to carry it out successfully, especially in the context of diverse generations of workers. This research shows that change management implementations can be used in organizations, with the specific aim of improving and supporting Generation Z employees' well-being at work. This article also identifies important factors that affect the well-being of Generation Z employees, as well as how these implementations can be used to address these issues. In addition to helping manage resistance to change, these implementations help create an inclusive and supportive work environment. As a result, Generation Z's engagement and productivity increased.  In this article, organizational leaders will discover effective ways to create and implement change management implementations by considering the needs and expectations of Generation Z as an important part of the company's successMental Health and Religious Observance in Adolescent Boys.